Two-stage wicking of yarns at the fiber scale investigated by synchrotron X-ray phase-contrast fast tomography. Issue 23 (December 2019) - Yoiti Ito Parada, Marcelo; Matthias Schlepütz, Christian; Michel Rossi, René; Derome, Dominique; Carmeliet, Jan
With synchrotron X-ray phase-contrast computed tomography, we document the wicking process at the fiber scale in cotton, polyethylene terephthalate and polypropylene yarns. A new segmentation procedure is developed, allowing a clear separation of the water and the fiber in the reconstructed images. From the water configurations, we obtain moisture content profiles over the height of the yarn and time-resolved three-dimensional visualization of the wicking process. The water filling over the height of the yarn is highly non-uniform, since the available pore space varies strongly along the yarn due to the twisting of the yarn. For the first time, a wicking in two stages is observed: an initial fast unsaturated wetting along the fiber direction followed by a main saturated flow characterized by large jumps in moisture content at discrete time steps. These jumps occur when large pore segments become filled suddenly from multiple entry points through small size throats connecting different pore segments.